Maternal and perinatal aspects of birth defects: a case-control study - Geiza Cesar Nhoncanse; Carla Maria R. Germano; Lucimar Retto da S. de Avo; Debora Gusmao Melo (Sociedade de Pediatria de São Paulo, 2014)
Objective: To assess the prevalence of congenital defects and to investigate their maternal and perinatal associated aspects by reviewing Birth Certificates. Methods: Among all born alive infants from January 2003 to December 2007 in Maternidade da Santa Casa de Misericórdia of São Carlos, Southeast Brazil (12,199 infants), cases were identified as the newborns whose Birth Certificates registered any congenital defect. The same sex neonate born immediately after the case was chosen as a control. In total, 13 variables were analyzed: six were maternal related, three represented labor and delivery conditions and four were linked to fetal status. The chi-square and Fisher's exact tests were used to compare the variables, being significant p<0.05. Results: The prevalence of congenital defects was 0.38% and the association of two or more defects represented 32% of all cases. The number of mothers whose education level was equal or less than eight years was significantly higher among the group with birth defects (p=0.047). A higher frequency of prematurity (p<0.001) and cesarean delivery (p=0.004) was observed among children with birth defects. This group also showed lower birth weight and Apgar scores in the 1st and the 5th minute (p<0.001). Conclusions: The prevalence of congenital defect of 0.38% is possibly due to underreporting. The defects notified in the Birth Certificates were only the most visible ones, regardless of their severity. There is a need of adequate epidemiological monitoring of birth defects in order to create and expand prevention and treatment programs.